2017
DOI: 10.1080/16546628.2017.1330096
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic acid suppresses adipogenesis, lipolysis in 3T3-L1 adipocytes, lipopolysaccharide-stimulated tumor necrosis factor-α secretion in macrophages, and inflammatory mediators in 3T3-L1 adipocytes

Abstract: Background: Rosmarinic acid (RA) is a natural phenol carboxylic acid with many promising biological effects. It may be a suitable candidate for improving obesity-related adipose tissue dysfunction.Objective: We aimed to investigate the therapeutic use of RA as an anti-obesity agent by measuring its effects on adipogenesis, lipolysis, and messenger RNA (mRNA) expression of major adipokines in 3T3-L1 adipocytes; and its effects on lipopolysaccharide (LPS)-induced tumor necrosis factor-α (TNF-α) secretion in macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 49 publications
0
11
1
Order By: Relevance
“…In the present study, we treated the chondrocytes with IL-1β, as expected, the expression of ADAMTS-4 and ADAMTS-5 was increased after incubation with IL-1β, and the production of IL-6, an inflammatory cytokine, was also upregulated by IL-1β. RosA is known to exhibit anti-inflammatory activities, Rui and others (Rui et al, 2017) reported that RosA inhibited the expression of IL-6 in 3T3-L1 adipocytes. Our results showed that RosA can inhibit the secretion of IL-6.Therefore, the protective effects of RosA on chondrocytes may be partly associated with its antiinflammatory properties.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, we treated the chondrocytes with IL-1β, as expected, the expression of ADAMTS-4 and ADAMTS-5 was increased after incubation with IL-1β, and the production of IL-6, an inflammatory cytokine, was also upregulated by IL-1β. RosA is known to exhibit anti-inflammatory activities, Rui and others (Rui et al, 2017) reported that RosA inhibited the expression of IL-6 in 3T3-L1 adipocytes. Our results showed that RosA can inhibit the secretion of IL-6.Therefore, the protective effects of RosA on chondrocytes may be partly associated with its antiinflammatory properties.…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, the present study also demonstrated the presence of high levels of gallic acid and rosmarinic acid in fermented HC. Many studies showed that quercetin [54,55], rosmarinic acid [56], chlorogenic acid [57], rutin [58], and gallic acid [59] exhibited potential antioxidant, anti-inflammatory, and antidiabetic properties.…”
Section: Discussionmentioning
confidence: 99%
“…The results reflect what already happened in adipose tissue; there was a high level of glycerol and FFAs with a reduction of triglyceride levels in the blood of experimental rats that have been received FSK alone or with mevastatin during the experimental period ( Table 4 ). It has been approved that FSK stimulates glycerol and free fatty acids release from animal adipocytes [ 35 ], human adipose tissue [ 36 ], adipocytes cell lines [ 37 , 38 ], and mice adipose tissue [ 39 ]. Recently, FSK has been used as a new supplement for controlling obesity [ 40 ] while it has been found that FSK can decrease total body lipids percentage; this comes with an improvement for lean body mass [ 41 ]; this comes in the same line of our results.…”
Section: Discussionmentioning
confidence: 99%